Tourism climate index on the Co To islands of Quang Ninh province, Vietnam - Nguyen, Thu-Nhung; Pham, Hoang-Hai; Pham, Van-Manh; Nguyen, Manh-Ha (Vietnam Journal of Marine Science and Technology, 2020)
Tourism is one of the spearhead economic sectors of every country in the world and sensitive to weather conditions. The climate is one of the most important factors for each destination for vacation and recreation. Almost the measures are primarily based on particular local weather and climate, and part of them deals with energy balance estimation to assess thermal comfort. Tourism climate indicator developed by Mieczkowski (1985) incorporates 7 climate variables (average temperature, maximum temperature, average humidity, minimum humidity, precipitation, number of sunny hours, wind speed) relevant to general tourism activities is used to assess potential impacts of climate change on tourism climate resources of Co To islands in the Tonkin Gulf of Vietnam. The monthly tourism climate indicator classification results show that the tourism potentials of Co To islands range from unfavorable (30–39) to very good (70–79) in March, April, November and December. Daily tourism climate indicator classification results indicate that tourism potentials are from extremely unfavorable (20–29) to excellent (80–89). The days at very good to excellent for travel are on 2nd, 3rd, 5–7th of January; 6–8th and 20–28th of February; 1st–8th, 12–17th and 20–28th of March; 1st–2nd,4–13th, 15–18th of April; 21st–24th of September; 1st–4th, 6th, 8–10th, 12th, 13th of November; 1st–26th of December. These findings are important for future research in assessing current and future climate suitability for sustainable tourism development.